Morphological and morphometric measurement of the temporomandibular joint of small and medium-weight dogs with different skull shapes - Quadflieg, Ina; Volk, Holger A.; Sake, Björn; Metje, Benjamin (Frontiers in Veterinary Science, 2024)
Background: The recognition and diagnosis of canine temporomandibular joint (TMJ) disease can be a challenge, often leaving them undiagnosed. Although computed tomography (CT) has proved to be highly efficacious in detecting joint disease in the TMJ, morphometric and morphological studies of the normal TMJ have been scarce. Especially, skull type specific anatomical differences of the TMJ in dogs of different weights and skull morphologies have received limited attention. Objective: This study aimed to compare the TMJ morphologies of dogs across different weight classes and skull types. Study design: retrospective study Methods: CT scans were used to measure the depth and width of the Fossa mandibularis and two angles between the Fossa mandibularis and the Caput mandibulae in a total of 92 dogs and 182 mandibular joints, respectively. Result: The TMJ varied in terms of weight groups and skull indices. Shallow mandibular pits, underdeveloped retroarticular processes, and reduced joint congruency were observed particularly in light-weight and brachycephalic dogs. Conversely, dolichocephalic animals displayed deep joint pits, pronounced joint congruency, and a well-developed Processus retroarticularis. Main Limitations: Observer learning curve; not every skull shape was represented in each weight group.